Fractal study on pore structure of tight sandstone based on full-scale map. (3rd October 2019) - Zhao, X.; Yang, Z.; Lin, W.; Xiong, S.; Luo, Y.; Liu, X.; Xia, D.
The pore characteristics of tight sandstones are of great significance for studying the size distribution, surface roughness and seepage mechanism. In order to evaluate the pore size distribution and pore comprehensive fractal characteristics of tight sandstone in Y Basin, the pore structure of tight sandstone is characterised by low temperature nitrogen adsorption (LTNA) and high pressure mercury intrusion (HPMI), and fractals of different scales are fitted and calculated. We calculate the pore comprehensive fractal dimension of tight sandstone based on the full-scale map and discuss the difference in pore roughness from the shale in the Qinshui Basin. Finally, we also studied the relationship between comprehensive fractal dimension and permeability and porosity. Our results suggest that the pore radius of tight sandstones is distributed between 2 nm to 1, 000 nm, and the surface of the macropores (> 100 nm) is rougher and more complex than the small pores (< 100 nm). The pore structure of the tight sandstone in the Y Basin is generally simpler than that of the shale in the Qinshui Basin. Besides, there is no significant correlation between the comprehensive fractal dimension and the permeability and porosity, suggesting the fractal dimension is not affected by porosity and permeability. [Received: September 11, 2018; Accepted: December 17, 2018]